2022
DOI: 10.1002/cpt.2711
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Clinical Decision Support: A Scoping Review

Abstract: Clinical decision support (CDS) is often cited as an essential part of pharmacogenomics (PGx) implementations. A multitude of strategies are available; however, it is unclear which strategies are effective and which metrics are used to quantify clinical utility. The objective of this scoping review was to aggregate previous studies into a cohesive depiction of the current state of PGx CDS implementations and identify areas for future research on PGx CDS. Articles were included if they (i) described electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 70 publications
(158 reference statements)
0
2
0
Order By: Relevance
“…A scoping review of PGx CDS alerts found clinical response was reported in 7 of 10 articles included and ranged from 19.5% to 71% 46 . The study that found a clinical response rate of 71% may not be an accurate representation due to a limited sample size ( n = 7 alerts) 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A scoping review of PGx CDS alerts found clinical response was reported in 7 of 10 articles included and ranged from 19.5% to 71% 46 . The study that found a clinical response rate of 71% may not be an accurate representation due to a limited sample size ( n = 7 alerts) 47 .…”
Section: Discussionmentioning
confidence: 99%
“…to 71%. 46 The study that found a clinical response rate of 71% may not be an accurate representation due to a limited sample size (n = 7 alerts). 47 Herr et al found recommendations were followed 42% of the time, which is more than double the recommendation acceptance rate observed in this study.…”
Section: Articlementioning
confidence: 99%
“…Data quality, computational processing, and standardization have all reached a point where third-party, EHR-integrated CDS tools can improve clinical care in oncology through the strategies described (Fig 1B). Recent studies have investigated the impact of deploying CDS and identified potential areas for improvement, 3,7,11,33,39 a necessary next step to enhance value for clinicians and patients. However, real-world assessments of CDS tools in oncology are limited.…”
Section: The Time Is Now To Start Moving From Molecular Information D...mentioning
confidence: 99%